Homelessness and Public Space: A Case Study of the City of Alcalá de Henares - Rubio-Martín, María José (Acciones e Investigaciones Sociales, 2021)
In the framework of the sociology of homelessness, it has been argued that the increasing expansion of economic neoliberalism leads to a new criminalisation and segregation of homeless people. This process is materialised, among other ways, through the control and regulation of public space. Through a case study, this article presents exploratory research carried out in Alcalá de Henares (Madrid). The research methodology combines quantitative data (obtained from the only source of data on homelessness that exists in this city), and qualitative information collected through semi-structured interviews and non-participant observation. The results show a progressive "expulsion" of homeless people from the city centre to the most degraded areas of the city. At the same time, this process coexists with social actions that try to attend to these people. There is a tense situation between different actors and interests in relation to public space, which should be addressed in order to guarantee everyone’s right to the city and to counteract attitudes of rejection towards the most extreme poverty.